'Mountains & Seas': A Percy Bysshe Shelley Letter to Leigh Hunt and Byron's 'Epistle to Augusta'. (3rd July 2017) - Webb, Timothy
Abstract: When Leigh Hunt and his family finally arrived at Genoa in June 1822 he exchanged letters with Percy Shelley, who was spending the summer at nearby Lerici. Shelley welcomed the Hunts, affectionately writing: 'may [traditionally interpreted as 'many'] mountains & seas no longer divide those whose affections are united'. Hunt was delighted by this friendly message but misrepresented its wording both in 1828 and in the two much later versions of his Autobiography . What he could not have known, and what was concealed by his own choice of phrasing, was that, whether consciously or not, Shelley was following the words of Byron's 'Epistle to Augusta', which had been written in 1816 but was not published till 1830. During the summer of 1816 when both Shelleys had been very close to Byron, Shelley almost certainly had opportunities to familiarize himself with the words in question. It was Shelley, too, who had been chosen by Byron to deliver the poem to his publisher, although Murray was firmly instructed not to publish without the consent of Augusta Leigh.